Production and characterization of a high molecular weight levan and fructooligosaccharides from a rhizospheric isolate of Bacillus aryabhattai - TOKSOY ÖNER, EBRU (ELSEVIER, 2020)
Bacillus aryabhattai GYC2-3 strain, capable of synthesizing EPS, was isolated from the rhizosphere of Taraxacum spp. plant. The EPS was identified as levan by C-13 NMR spectroscopy and methylation analysis. The levan produced had a high weight average molecular weight of 5.317 x 10(7) Da and degree of branching 5.19%. Thin layer chromatography and high-performance anion-exchange chromatography revealed that it is capable of producing broad range of fructooligosaccharides (FOS) and higher levels of FOS synthesis were observed with increasing sucrose concentrations. The optimum temperature, initial pH and sucrose concentration for levan biosynthesis were studied to be 30 degrees C, 8.0 and 250 g/L, respectively. Levan production was increased by similar to 38% (26 g/L) when provided aeration as compare to static cultures. To the best of our knowledge, this is the first report on biosynthesis of levan and FOS by a B. aryabhattai strain.
Keywords: Bacillus aryabhattai; Levan; Fructooligosaccharides; Exopolysaccharide; Prebiotics; STRUCTURAL-CHARACTERIZATION; FRUCTANSUCRASE ENZYMES; LEVANSUCRASE; OPTIMIZATION; STRAIN